Use of pineapple peel as adsorbent of r40 (typical dye in food industry) - Urrego Durango, Viviana Liseth
The effect of different operating parameters on the adsorption of R40 (diluted in an aqueous matrix) on pineapple peels was studied. It was found that pineapple peels can remove up to 84% of the colorant, a value lower than that achieved using commercial activated carbon as adsorbent (removal close to 99%), but with the advantage that pineapple peels do not require chemical neither thermal processes for their manufacture, and represent the valuation of agroindustrial wastes. The variables analyzed inlcuded the amount and particle size of the adsorbent, the operating time and temperatura. The higher percentages of dye removal were adquired by using 150 mg of adsorbent, particle sizes between 0.125 and 180 mm and 5 h of operation. Apparently the temperature does not have a significant effect on the phenomenon within the ranges analyzed (25-45 ° C). It is expected that the results obtained contribute to the development of agroindustrial processes where there is a valuation and rational use to agroindustrial wastes such as pineapple peels.